For Increasing Work Efficiency of Employees in Enterprises (American Journal of Public Diplomacy and International Studies (2993-2157), 2024)
The article highlights the role of managerial work of managers in the effective operation of enterprises, the scientific approaches of scientists in this regard, and estimated indicators.